Factors affecting career orientation: indigenous ethnic minority students in Vietnam’s Central Highlands - Hai, Phung Viet; Xuan, Tran Thi Huong; Loan, Phung Thi To; Phuong, Nguyen Thi Thanh (Institute of Advanced Engineering and Science, 2025)
Career orientation competency (COC) plays a crucial role in preparing students for lifelong learning and labor market adaptability. However, existing research has largely overlooked how this competency develops among indigenous ethnic minority students in culturally diverse and educationally disadvantaged contexts such as Vietnam’s Central Highlands. Addressing this gap, the present study adopts the social cognitive career theory (SCCT) to examine how personal, contextual, and behavioral factors interact to shape COC in this population. SCCT serves not only as a conceptual lens but also informs the development of the research model and interpretation of findings. A quantitative approach was employed using cross-sectional survey data collected from 669 ethnic minority students. Analytical techniques included reliability analysis (Cronbach’s alpha), exploratory factor analysis (EFA) for construct validation, and multiple linear regression to test predictive relationships. Results revealed six key determinants of COC: self-awareness (SA), expectations for results (ER), personal goals (PG), community connection (CC), career exploration (CE), and cultural identity (CI). Notably, CI had the most significant effect (β=0.308), suggesting its central role in guiding career-related behaviors. These findings have important implications for both theory and practice. They extend SCCT by integrating culturally specific constructs relevant to marginalized communities and they highlight the need for context-responsive career guidance programs that recognize and leverage students’ cultural identities. The study contributes to the empirical foundation for inclusive education policy reforms targeting ethnic minority youth in Vietnam.